LEGAL CONSTRUCTION OF ZAKAT BASED ON LAW NUMBER 23 OF 2011 CONCERNING ZAKAT MANAGEMENT - Rahmat Fauzi; Ahmad Rofiq; Sri Kusriyah; Anis Mashdurohatun (LPPM STIH Putri Maharaja, 2025)
This study aims to ascertain the Legal Construction of Zakat Management as stated in Law Number 23 of 2011 on Zakat Management. This research uses a juridical-normative approach, a methodology grounded in laws and regulations, and theories and concepts about the scope of zakat rules stated in statutes. Originating in Indonesian Islamic teachings, Legislation Number 23 of 2011 about Zakat Management declared Zakat a beneficial law. Zakat's status as a particular worship has enormous potential to enhance the well-being of Muslims in Indonesia if it is properly administered and applied. According to the study's findings, Law Number 23 of 2011 concerning Zakat Management ought to be able to enhance the effectiveness and efficiency of Zakat management services and the benefits of Zakat in reducing poverty and promoting community welfare. This law strengthens the institutional framework for managing integrated zakat into a single integrated unit, enabling BAZNAS (Provincial and Regional BAZNAS) to become the sole institution with zakat authority and LAZ to support the enforcement of zakat collection, distribution, and utilization. Thanks to this law, institutions that collect zakat will be able to do so more effectively. The application of fines in Aceh to zakat payers (muzakki) who do not want to fulfil their obligations by paying zakat, which has been regulated in Aceh Qanun Number 10 of 2007 concerning Baitul Mal, as the true implementation of Islamic law. The provisions of this sanction cannot be applied in Law Number 23 of 2011 concerning Zakat Management because the Indonesian state is based on Pancasila, not on Islam, unlike Aceh, which is a special autonomous region. In the zakat law, fines can only be given to amil who commits irregularities and misuse of zakat funds, because this is included in criminal acts.